PREDICTORS OF MORTALITY AFTER ACUTE STROKE A PROSPECTIVE HOSPITAL BASED STUDY - Rathore, Javed Akhter; Kango, Zulfiqar Ali; Mehraj, Adnan (Journal of Ayub Medical College Abbottabad, 2011)
Background: The stroke is third leading cause of death in world and 10% of patients with an acute ischemic stroke die within 30 days. Various clinical variables have been implicated as predictors of final outcome of acute stroke. The study was aimed to identify predictors of mortality after an acute stroke. Material and Methods: This prospective study included 149 consecutive patients of acute Hospital Muzaffarabad, Azad Kashmir. The outcome as mortality measures used were Modified Ranking Scale (mRS) and Glasgow Coma Scale (GCS). Examination included clinical, neurological evaluation, laboratory tests, and brain CT. The follow-ups at 14 days were done for all patients. Results: Hospital mortality was 17.4 % (26/149) within 14 days. Age and gender had no impact on mortality. Hypertension (p=0.008), smoking (p=0.056)), brain infarction (p=<0.001), hemorrhagic stroke (p=<0.001), diabetes (p=0.292), atrial fibrillation (p<0.001), high mRS (p<0.001), low GCS score (p<0.001), on admission were important predictors of mortality. Conclusions: We report 17.4% mortality at 14 days. Mortality associated with acute stroke needs prevention and control of risk factors. Keywords: acute stroke; predictors; mortality, Glasgow Coma Scale, Modified Ranking Scale